β-Cell keratin 8 maintains islet mechanical integrity, mitochondrial ultrastructure, and β-cell glucose transporter 2 plasma membrane targeting - Baghestani, Sarah; Haldin, Caroline; Kosijer, Petar; Alam, Catharina M.; Toivola, Diana M. (AMER PHYSIOLOGICAL SOC, 2025)
Islet β-cell dysfunction is an underlying factor for type I diabetes (T1D) development. Insulin sensing and secretion are tightly regulated in β-cells at multiple subcellular levels. The epithelial intermediate filament (IF) protein keratin (K) 8 is the main β-cell keratin, constituting the filament network with K18. To identify the cell-autonomous functions of K8 in β-cells, mice with targeted deletion of β-cell K8 (K8flox/flox; Ins-Cre) were analyzed for islet morphology, ultrastructure, and integrity, as well as blood glucose regulation and streptozotocin (STZ)-induced diabetes development. Glucose transporter 2 (GLUT2) localization was studied in β-cells in vivo and in MIN6 cells with intact or disrupted K8/K18 filaments. Loss of β-cell K8 leads to a major reduction in K18. Islets without β-cell K8 are more fragile, and these β-cells display disjointed plasma membrane organization with less membranous E-cadherin and smaller mitochondria with diffuse cristae. Lack of β-cell K8 also leads to a reduced glucose-stimulated insulin secretion (GSIS) response in vivo, despite undisturbed systemic blood glucose regulation. K8flox/flox, Ins-Cre mice have a decreased sensitivity to STZ compared with K8 wild-type mice, which is in line with decreased membranous GLUT2 expression observed in vivo, as GLUT2 is required for STZ uptake in β-cells. In vitro, MIN6 cell plasma membrane GLUT2 is rescued in cells overexpressing K8/K18 filaments but mistargeted in cells with disrupted K8/K18 filaments. β-Cell K8 is required for islet and β-cell structural integrity, normal mitochondrial morphology, and GLUT2 plasma membrane targeting, and has implications on STZ sensitivity as well as systemic insulin responses.